Electrochemical biosensors for the determination of toxic substances related to food safety developed in south America: Mycotoxins and herbicides - Fernández, Héctor (2017)
The goal of achieving food safety and quality has become increasingly important in relevant areas. The achievement of this objective includes a significant effort in different areas related to the production of raw materials, storage, transportation, etc. One of the central areas in the verification of food safety and food quality control is related to the analysis of food components and, in particular, possible toxic substances that they may contain. Therefore, the demand for appropriate methods for the determination of these substances is increasingly demanding. Thus, not only is accuracy and precision sought in the results of the analysis, but also the speed, simplicity and lowering of costs. In this way, electrochemical techniques and, particularly, electrochemical biosensors have emerged in recent times as good candidates to satisfy such requirements. This review summarizes the advances made in research and development centers located in South American countries related to the development of electrochemical biosensors for the determination of toxic substances present in foods, particularly mycotoxins and herbicides.